2016
DOI: 10.17221/79/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal manipulation during late incubation period on post-hatch thermotolerance in ostrich

Abstract: ABSTRACT:The effects of thermal manipulation (TM) during late ostrich embryonic development on hatchability, body weight, biochemical and hormonal changes, and the ability of hatching chicks to cope with thermal challenge in days 6-8 of age were examined. At 35 days of incubation, two hundred fertile eggs were weighed and divided into two equal groups with five replicates. The first group was exposed to 36.5°C and 25% relative humidity (RH) (control), while the second group was exposed to 38.5°C and 45% RH for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…This confliction can be attributed to the incubation period differences in the current study contrasted with other reports. The significant increase in weights of liver and heart tissues as a result of TM in the current study disagrees with previours reports in ostrrish [26] and Egyptian chickens [27] exposed to high incubation temperature during their late embryonic life. The significant increase in the breast muscles of birds exposed to TM of the current study are in the line with that obesreved earlier [10, 28] in the broiles chickens.…”
Section: Discussioncontrasting
confidence: 99%
“…This confliction can be attributed to the incubation period differences in the current study contrasted with other reports. The significant increase in weights of liver and heart tissues as a result of TM in the current study disagrees with previours reports in ostrrish [26] and Egyptian chickens [27] exposed to high incubation temperature during their late embryonic life. The significant increase in the breast muscles of birds exposed to TM of the current study are in the line with that obesreved earlier [10, 28] in the broiles chickens.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to controls, TM chicks were found to have a reduced hatchability rate in the current study. In other avian species like ostriches and Japanese quail, TM resulted in a similarly decreased hatchability rate [39,40]. However, mixed findings were reported for the effect of TM on broiler hatchability, as some studies found that TM positively or negatively affected the hatchability rate [31,[41][42][43], while others reported no effect [36,[43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the respiratory rate of the birds appeared to be dose-dependent. Body temperature is an excellent measure of metabolic rate and is associated with acclimatization [ 55 ]. An increase in respiration rate in birds exposed to heat stress has been reported to decrease the blood HCO3- and PCO2 and increase blood pH, resulting in respiratory alkalosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%